Analysis of Building Damage and Reliability in Ensuring Safety, Health, Comfort, and Convenience for Users - noverma (Journal of Green Science and Technology, 2023)
A functional building is a building that can provide security, comfort, health, and convenience for its users. This can be measured by analyzing the level of damage to buildings and their reliability. A building may suffer damage from time to time due to aging, therefore regular inspection and maintenance is required to assess the intensity of the damage and its level of reliability. The purpose of this research is to determine the level of damage and reliability of the building in order to ensure safety, comfort, health, and convenience for users. The research was conducted through field observations of architectural, structural, utility, accessibility, as well as building and environmental aspects based on Ministerial Regulation No. 16/PRT/M/2010, Ministerial Regulation No. 29/PRT/M/2006, and Ministerial Regulation No. .26/PRT/M/2008, as well as relevant studies. The analysis was carried out using a quantitative weighting system, calculating the percentage of the damaged quantity to the total quantity. The results showed that the building suffered mild to moderate damage with reliability classified as less reliable and unreliable. Recommendations based on the level of damage and reliability of the building include rehabilitation (repairing damage without changing function), renovation of unreliable aspects (repairing damage that can change function), and re-function or redesigning of unreliable aspects.